Interfibril hydrogen bonding improves the strain-rate response of natural armour. Issue 150 (31st January 2019) - Arola, D.; Ghods, S.; Son, C.; Murcia, S.; Ossa, E. A.
Abstract : Fish scales are laminated composites that consist of plies of unidirectional collagen fibrils with twisted-plywood stacking arrangement. Owing to their composition, the toughness of scales is dependent on the intermolecular bonding within and between the collagen fibrils. Adjusting the extent of this bonding with an appropriate stimulus has implications for the design of next-generation bioinspired flexible armours. In this investigation, scales were exposed to environments of water or a polar solvent (i.e. ethanol) to influence the extent of intermolecular bonding, and their mechanical behaviour was evaluated in uniaxial tension and transverse puncture. Results showed that the resistance to failure of the scales increased with loading rate in both tension and puncture and that the polar solvent treatment increased both the strength and toughness through interpeptide bonding; the largest increase occurred in the puncture resistance of scales from the tail region (a factor of nearly 7×). The increase in strength and damage tolerance with stronger intermolecular bonding is uncommon for structural materials and is a unique characteristic of the low mineral content. Scales from regions of the body with higher mineral content underwent less strengthening, which is most likely the result of interference posed by the mineral crystals to intermolecular bonding. Overall, the results showed that flexible bioinspired composite materials for puncture resistance should enrol constituents and complementary processing that capitalize on interfibril bonds.